Takashi Shimura : chameleon of Japanese cinema - Nollen, Scott Allen (McFarland & Company, Inc., Publishers, 2019)
"Considered one of the finest performers in world cinema, Japanese actor Takashi Shimura (1905-1982) appeared in more than 300 stage, film and television roles during his five-decade career. This is the first complete English-language account of Shimura's work. In addition to historical and critical coverage of Shimura's life and career, it includes an extensive filmography"--